Characterization of endothelial cells using electrochemical impedance spectroscopy - Liu, Fei; Arifuzzaman, S. M.; Nordin, Anis Nurashikin; Spray, David; Voiculescu, Ioana (2010)
In this paper we report on the electrical impedance spectroscopy characterization of endothelial cell lines (RFPEC). For electrical cell-substrate impedance sensing (ECIS) of the endothelial cells a commercially available eight-well cell culture impedance array (ECIS-8W1E) was used. The impedance measurements were recorded with cell culture medium (without cells) and with endothelial cell layer in the culture medium over a frequency range from 100 Hz to 100 kHz. The impedance measurements were compared to the equivalent circuit model. The impedance measurements of endothelia cells were also simulated using COMSOL Multiphysics #x2122;, a commercially available modeling package.